2022
DOI: 10.1101/2022.11.04.22281798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale Analyses of CAV1 and CAV2 Suggest Their Expression is Higher in Post-mortem ALS Brain Tissue and Affects Survival

Abstract: Caveolin-1 and Caveolin-2 (CAV1 and CAV2) are proteins associated with intercellular neurotrophic signalling. There is converging evidence that CAV1 and CAV2 (CAV1/2) genes have a role in ALS. Disease-associated variants have been identified within CAV1/2 enhancers, which reduce gene expression and lead to disruption of membrane lipid rafts. Using large ALS whole-genome sequencing and post-mortem RNA sequencing datasets (5987 and 365 tissue samples, respectively), and iPSC-derived motor neurons from 55 individ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(63 reference statements)
1
0
0
Order By: Relevance
“…A recent study reported a noncoding repeat polymorphism in the same domain as being protective against ALS 30 , suggesting an intricate genetic architecture in this domain with different classes of variants playing different roles. In recent years, several studies have shown that noncoding variants have a major role in ALS: for example, enhancer variants in CAV1 and CAV2 31,32 and intronic variants in UNC13A 33,34 . Our findings expand this by also implicating NEFH noncoding variants in ALS.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study reported a noncoding repeat polymorphism in the same domain as being protective against ALS 30 , suggesting an intricate genetic architecture in this domain with different classes of variants playing different roles. In recent years, several studies have shown that noncoding variants have a major role in ALS: for example, enhancer variants in CAV1 and CAV2 31,32 and intronic variants in UNC13A 33,34 . Our findings expand this by also implicating NEFH noncoding variants in ALS.…”
Section: Discussionsupporting
confidence: 84%